Analisis Pengaruh Product Quality dan Social Media Marketing terhadap Consumer Loyalty dengan Costomer Satisfaction sebagai Variabel Intervening pada Lawoek Coffee Temanggung - Lilik Meliana; Muinah Fadhilah; Putri Dwi Cahyani (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
The purpose of this study is to overcome the gap in previous research between the effect of product quality and social media marketing on consumer loyalty. This research is classified as a quantitative study. The sampling technique used in this study used a non-probability sampling technique, namely purposive sampling. The number of samples used in this study were 100 respondents who had visited and made purchases more than twice at Lawoek Coffe Temanggung. Data were processed using SPSS software version 29. Data analysis used multiple linear regression analysis and Sobel test. The results of this study indicate that; (1) product quality has a significant effect on consumer satisfaction with a t-value of 6.251. With sig. of < 0.001 means < 0.05. (2) social media marketing has a significant effect on consumer satisfaction with a t-count of 5.458. With sig. of < 0.001 means < 0.05. (3) consumer satisfaction has a significant effect on consumer loyalty with a t-count of 3.681. With sig. of < 0.001 means < 0.05. (4) product quality has a significant effect on consumer loyalty with a t-count of 3.527. With sig. of < 0.001 means < 0.05. (5) social media marketing has no significant effect on consumer loyalty with a t-count of 1.505. With sig. of 0.136 means > 0.05. (6) consumer satisfaction is able to mediate the effect of product quality on consumer loyalty with a sobel value of 3.18329960 meaning > 1.983 and (7) consumer satisfaction is able to mediate the effect of social media marketing on consumer loyalty with a sobel value of 3.05927598 meaning > 1.983. Keywords: Product Quality, Social Media Marketing, Consumer Satisfaction, Consumer Loyalty